2008
DOI: 10.1021/jo800528y
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Lithium Ketone Enolate Aggregation in the Gas Phase and in THF Solution

Abstract: The aggregation state of several lithium enolates were calculated in the gas phase and in THF solution by the B3LYP DFT and MP2 methods. The gas phase free energies of aggregate formation were underestimated by the DFT calculations, compared to those obtained by the G3MP2 method, although DFT did correctly predict the hexamer to be the major gas phase species. The DFT calculations correctly predicted the tetramer to be the major species in THF, while MP2 underestimated the stability of the tetramer relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
(74 reference statements)
4
20
0
Order By: Relevance
“…These calculations were performed in the presence of dimethylether (DME) molecules to saturate the coordination sphere of lithium cation. In good agreement with the results obtained by Pratt et al, [33] kinetically stable structures were obtained for the different aggregates ( Figure 2).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These calculations were performed in the presence of dimethylether (DME) molecules to saturate the coordination sphere of lithium cation. In good agreement with the results obtained by Pratt et al, [33] kinetically stable structures were obtained for the different aggregates ( Figure 2).…”
Section: Resultssupporting
confidence: 91%
“…[35] When we tried to optimize the fully Me 2 O-solvated hexameric structures only the hexagonal-prismatic geometry A C H T U N G T R E N N U N G (1 a-Li) 6 was obtained starting from both structures ( Figure 3). This latter structure is similar to THF-solvated geometries obtained by Pratt et al [33] We postulated that bonding within the Li n O n clusters should have a significant ionic character. To test this hypothesis we measured the sign of the Laplacian of electron density at the O À Li bond critical point of electron density of 1 a-Li and A C H T U N G T R E N N U N G (1 a-Li) 2 .…”
Section: Resultssupporting
confidence: 88%
“…It was found that B3LYP underestimates the gas-phase dimerization energy of lithium methoxide rather strongly (4-5 kcal mol −1 , corresponding to about 7%) compared to (coupledcluster with full treatment of singles and doubles and approximate inclusion of triples contribution) CCSD(T) calculated energies, while MP2 performed slightly better. A similar interaction underestimation was found by Pratt and coworkers [97] studying lithium enolates. In addition, in the previously discussed study by Khartabil and coworkers on the O-Li bond in the solvated monomers of lithium methoxide, only B3LYP and MP2 were used.…”
Section: Lithium Alkoxides and Lithium Amidessupporting
confidence: 85%
“…This is consistent with previously published studies. [19][20][21][22] The free energies of gas-phase mixed aggregate formation calculated by the B3LYP and MP2 methods are in good agreement, generally within 1-2 kcal mole À1 of each other. Although the gas-phase calculations are valuable for comparison of different computational methods and for predicting the structures and aggregation states in non-polar solvents, the negligible solubility of lithium chloride in those solvents makes it unlikely that these mixed aggregates will be observed in solution.…”
Section: Resultsmentioning
confidence: 69%
“…Comparison of the two tables shows that the formation of higher mixed aggregates is most energetically favorable in the gas phase. This is consistent with previously published studies . The free energies of gas‐phase mixed aggregate formation calculated by the B3LYP and MP2 methods are in good agreement, generally within 1–2 kcal mole −1 of each other.…”
Section: Resultsmentioning
confidence: 99%